Trichobezoars: a hairy cause of intestinal obstruction - Tiwary, Anurag; Singhal, Pragati; Khan, Nida; Tiwary, Pramod (International Surgery Journal, 2020)
Trichobezoars are an infrequent form of bezoar found in the stomach or intestine, created from ingested hair. Their most frequent location is in the stomach but they may extend through the pylorus into the small bowel. This condition is known as Rapunzel syndrome. Trichobezoar with Rapunzel syndrome is an uncommon diagnosis in children. Authors report 3 cases of Rapunzel syndrome with a large bezoar in paediatric age group that presented with features of acute intestinal obstruction. They were managed with surgical exploration.